Trends in Mean Annual Streamflows in Serra da Mantiqueira Environmental Protection Area - Vilanova, Mateus Ricardo Nogueira (Instituto de Tecnologia do Paraná - Tecpar, 2014)
The aim of this study was to detect trends in the mean annual streamflow in watersheds of Serra da Mantiqueira Environmental Protection Area, an important Brazilian conservation area located between Minas Gerais, São Paulo and Rio de Janeiro States. Historical series of four selected streamgage stations were analyzed for the periods of 1980-1998 and 1980-2009, using the Mann-Kendall and Regional Mann-Kendall tests. The results showed that the mean annual streamflows of Serra da Mantiqueira Environmental Protection Area watersheds did not change during the complete period of 1980-2009. The tests detected statistically significant trends of reduction of mean annual streamflow during the 1980-1998 period. The confrontation of this result with the inexistence of rainfall trends during the same period suggested that the streamflow changes detected were consequences of changes in the watersheds physical characteristics, and/or increases in water abstraction for multiple uses.
Keywords: streamflow changes; Serra da Mantiqueira Range; Mann-Kendall test